Mid-infrared sensing of molecular vibrational modes with tunable graphene plasmons - Wu, Tingting (2017)
We study the tunable plasmons based on a graphene integrated gold grating structure to sense the vibrational modes of nanometric molecules. The greatly enhanced light-matter interaction and the broadband tunability of the localized graphene plasmonic resonance enable accurate label-free identification of the molecular vibrational modes at subwavelength scale. Our results may accelerate the further development of novel cost-effective biosensors with superior molecular chemical fingerprint sensitivity in an active graphene plasmonic device.